Simultaneous determination of human plasma protein binding of bioactive flavonoids in Polygonum orientale by equilibrium dialysis combined with UPLCâMS/MS - Yong Huang; Hui Chen; Feng He; Zhi-Rong Zhang; Lin Zheng; Yue Liu; Yan-Yu Lan; Shang-Gao Liao; Yong-Jun Li; Yong-Lin Wang (Elsevier, 2013)
A simple and selective ultra performance liquid chromatographyâelectrospray ionization tandem mass spectrometry (UPLCâESI-MS/MS) assay was developed for the determination of the human plasma protein binding of four bioactive flavonoids (such as orientin and vitexin) in Polygonum orientale. Protein precipitation was used for sample preparation. Equilibrium dialysis technique was applied to determine the plasma protein binding under physiological conditions. The separation was achieved through a Waters C18 column with a mobile phase composed of 0.1% formic acid in acetonitrile and 0.1% aqueous formic acid using step gradient elution at a flow rate of 0.35Â mL/min. A Waters ACQUITYâ¢ TQD system was operated under the multiple reaction monitoring (MRM) mode of positive electrospray ionization. All of the recovery, precision, accuracy and stability of the method met the requirements. Good correlations (r>0.99) of the four compounds were found, which suggested that these compounds can be simultaneously determined with acceptable accuracy. Results showed that the plasma protein bindings of the four bioactive flavonoids were in the range of 74â89% over the six concentrations studied. The binding parameters containing protein binding affinity, protein binding dissociation constant, and protein binding site were studied. The maximum ability to bind with protein was also determined in the assay in order to understand the drug-protein binding of each compound better. Keywords: Polygonum orientale, Plasma protein binding, Bioactive compounds, Equilibrium dialysis, UPLCâESI-MS/MS